PERANAN PEMBELAJARAN SEJARAH DALAM PENANAMAN SIKAP NASIONALISME SISWA KELAS XI IPS SMA NEGERI 1 PECANGAAN - Amelia, Citra (Indonesian Journal of History Education, 2015)
This study aims to: (1) Describe the implementation of the teaching of history in planting nationalism among students of class XI Social Science Pecangaan Senior High School. (2) Describe the attitude of nationalism class XI Social Science Pecangaan Senior High School. (3) Knowing the constraints faced by teachers in the planting of nationalism in history teaching class XI IPS SMAN I Pecangaan. (4) Describe the efforts of teachers in the face of constraints planting of nationalism in history teaching class XI Social Science Pecangaan Senior High School. This research method using qualitative research methods. Â